Ta có x + y =xy => x = xy - y => x = y(x-1)
Ta lại có x + y = x / y thay x = y(x-1) vào vế phải :
x+ y = y(x−1)y =x−1
=> x + y = x- 1 => y = -1
ta có x + y = xy
thay y = -1 vào ta có:
x + - 1 = -1 .x => x - 1 = -x => 2x = -1 => x = -1/2
VẬy y = -1 ; x = -1/2
xy=x:y
=>y2=x:x=1
=>y=1 hoặc y=-1
*)y=1 =>x+1=x(vô lí)
*)y=-1 =>x-1=-x
=>x=1/2
Vậy y=-1 x=1/2
xy = x/y <=> x = 0 hoặc y2 = 1
TH1: x = 0
=> 0 + y = 0 <=> y = 0 (loại)
TH2: y = 1
=> x + 1 = x <=> 1 = 0 (loại)
TH3: y = -1
=> x - 1 = -x <=> x = 1/2
=> x = 1/2 và y = -1